2012
DOI: 10.4161/cc.21770
|View full text |Cite
|
Sign up to set email alerts
|

4E-BP1 participates in maintaining spindle integrity and genomic stability via interacting with PLK1

Abstract: The essential function of eIF4E-binding protein 1 (4E-BP1) in translation initiation has been well established; however, the role of 4E-BP1 in normal cell cycle progression is coming to attention. Here, we revealed the role of 4E-BP1 on mitotic regulation and chromosomal DNA dynamics during mitosis. First, we have observed the co-localization of the phosphorylated 4E-BP1 at T37/46 with Polo-like kinase 1 (PLK1) at the centrosomes during. Depression of 4E-BP1 by small interfering RNA in HepG2 or HeLa cells resu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
39
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 39 publications
7
39
0
Order By: Relevance
“…We were also able to localize a portion of S83-phosphorylated 4E-BP1 at the centrosomes consistent with a previous report, which shows that 4E-BP1 knockdown leads to multipolar spindles and misaligned chromosomes (23). Further, S83 phosphorylation increased from prophase to metaphase and decreased thereafter, which is in agreement with nocodazole prometaphase synchronization results and with the timing of CDK1 activity (27).…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…We were also able to localize a portion of S83-phosphorylated 4E-BP1 at the centrosomes consistent with a previous report, which shows that 4E-BP1 knockdown leads to multipolar spindles and misaligned chromosomes (23). Further, S83 phosphorylation increased from prophase to metaphase and decreased thereafter, which is in agreement with nocodazole prometaphase synchronization results and with the timing of CDK1 activity (27).…”
Section: Discussionsupporting
confidence: 79%
“…Resistance of various cancers to mTOR inhibitor treatment indicates that other pathways are implicated in 4E-BP1 inactivation (14). Several serine/threonine kinases have been shown to phosphorylate 4E-BP1, such as p38 MAPK, ERK, PIM2, ATM, CDK1, PLK1, LRRK2, GSK3β, and CK1e (15)(16)(17)(18)(19)(20)(21)(22)(23). We recently demonstrated that cyclin-dependent kinase 1 (CDK1) phosphorylates 4E-BP1 at canonical sites T37, T46, S65, and T70 during mitosis and generates a high-molecularweight phospho-isoform called δ-4E-BP1, even in the absence of mTOR activity (24).…”
Section: Merkel Cell Polyomavirusmentioning
confidence: 99%
“…For instance, phosphorylation of 4EBP1 at these two distinct sites can be performed by CDK1 under conditions of reduced mTOR signaling (115). Likewise, PLK1 was shown to have similar effects in HepG2 (116). Furthermore, our data also indicated an increase in phosphorylation of mTOR at S2448, which, in this form, is known to be associated with mTORC1 complex (117) (Figure 1).…”
Section: Downstream Mechanisms Following Inhibition Of Hepatoblastomasupporting
confidence: 66%
“…Kinases associated with the spindle and cell cycle progression are obvious likely controllers. Kinases implicated in EIF4EBP1 phosphorylation include mTOR, polo-like kinases, cyclin-dependent cell division kinases, and several others (Lawrence et al 1997;Yang and Kastan 2000;Heesom et al 2001;Shang et al 2012). For example, PLK1-mediated phosphorylation in the region of human EIF4EBP1 residues 77-118, which includes Ser112, is accompanied by localization to spindles in mitotic cells.…”
Section: Mrna Enrichment At Spindles In Mouse Oocytes 355mentioning
confidence: 99%